A Fatal Sepsis Caused by Hyaluronate Knee Injection: How Much the Medical History and the Informed Consent Might Be Important? - F. Manfreda; G. Rinonapoli; A. Nardi; P. Antinolfi; A. Caraffa (Case Reports in Orthopedics)
The incidence of Osteoarthritis (OA) is gradually increasing worldwide due to two main reasons: longer life expectation and increased functional demand. Several treatment options have been proposed for this disease. Conservative treatment has the goal to improve the quality of life, reduce pain, and prevent the progression of the disease. Hyaluronate viscosupplementation is one of the most used infiltrative treatments for OA, but, despite its common use, clinical efficacy is still under question. Though adverse reactions for this medical option are actually rare, septic arthritis is a very scaring complication. We present a case report of a 59-year-old man who has been submitted to only one knee hyaluronate injection and consequently reported a severe septic arthritis and systemic sepsis, which lead to the death of the patient. We recommend producing correct guidelines for a clean aseptic procedure of injection to obtain proper consensus from the patient and to pay attention to his clinical history and comorbidities before acting any kind of invasive treatment, including joint injection.